Dental Age Estimation by Assessing the Pulp Volume of Five Teeth in a Peruvian Population Using Cone Beam Computed Tomography Images - Salvatierra Gálvez, Juliana Magaly (2026)
Dental age estimation is very important for individual identification in criminal and civil forensic investigations. One of the methods for age estimation is studying age related changes in pulp volume of teeth. The objective of the current study was to estimate dental age from the pulp volume of five different categories of teeth of a Peruvian sample using cone beam computed tomography (CBCT). Retrospective CBCT records of 231 patients [females (134), males (97), age: 12-60 years]  were included in the study, categorized into five different age groups (12-19, 20-29, 30-39, 40-49, 50-59, 60 years and older). Dental pulp volume of five categories of teeth(upper canines, left upper central incisors, left upper first molars, lower left first premolars, first molars) were analyzed using Romexis® 5.3.3.5 software for each patient. There was a reduction in the pulp volume of upper right and left canine with age. The pulp volume was lowest in people aged 60 years and over. Linear regression analysis of the pulp volume and chronological age showed a coefficient of determination of 30%, suggesting a weak correlation. A weak correlation between dental pulp and age is derived. But, a robust large homogenous sample of teeth in future for different age groups may establish a reliable regression equation.